Proceedings of the 5th International Conference on Education and Technology (ICET 2019) 2019
DOI: 10.2991/icet-19.2019.29
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis in the Community-Based School Transportation Service

Abstract: This study aims to analyze the magnitude of the costs and factors that influence the implementation of community-based school transportation services. Implementation of school transportation services as simple mass transportation as an effort to reduce congestion on the highway. The research method uses a qualitative approach with a case study research design. The location of the study was at Al-Falah Elementary School in Surabaya which enabled the community to maximize school-specific services to support the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The study found that the respondents agreed to a large extent (M=3.85, SD=0.828) on the transportation costs for students on academic trips in the school being high due to the school location. The results of this study are consistent with that of Trihantoyo, Sholeh and Setyowati (2019) in a study based on the cost analysis of the community based transportation services which noted that the school location impacted on the school transportation costs. The schools that were remotely located would incur higher costs in contexts where the required services are often centralized in urban areas.…”
Section: Discussionsupporting
confidence: 89%
“…The study found that the respondents agreed to a large extent (M=3.85, SD=0.828) on the transportation costs for students on academic trips in the school being high due to the school location. The results of this study are consistent with that of Trihantoyo, Sholeh and Setyowati (2019) in a study based on the cost analysis of the community based transportation services which noted that the school location impacted on the school transportation costs. The schools that were remotely located would incur higher costs in contexts where the required services are often centralized in urban areas.…”
Section: Discussionsupporting
confidence: 89%